The activity of a Hexameric M17 Metallo-Aminopeptidase is associated with survival of Mycobacterium tuberculosis - Corrêa, André França (2017)
Mycobacterium tuberculosis is one of the most prevalent human pathogens causing millions of deaths in the last years. Moreover, tuberculosis (TB) treatment has become increasingly challenging owing to the emergence of multidrug resistant M. tuberculosis strains. Thus, there is an immediate need for the development of new anti-TB drugs. Proteases appear to be a promising approach and may lead to shortened and effective treatments for drug-resistant TB. Although the M. tuberculosis genome predicts more than 100 genes encoding proteases, only a few of them have been studied. Aminopeptidases constitute a set of proteases that selectively remove amino acids from the N-terminus of proteins and peptides and may act as virulence factors, essential for survival and maintenance of many microbial pathogens. Here, we characterized a leucine aminopeptidase of M. tuberculosis (MtLAP) as a cytosolic oligomeric metalloaminopeptidase. Molecular and enzymatic properties lead us to classify MtLAP as a typical member of the peptidase family M17. Furthermore, the aminopeptidase inhibitor bestatin strongly inhibited MtLAP activity, in vitro M. tuberculosis growth and macrophage infection. In murine model of TB, bestatin treatment reduced bacterial burden and lesion in the lungs of infected mice. Thus, our data suggest that MtLAP participates in important metabolic pathways of M. tuberculosis necessary for its survival and virulence and consequently may be a promising target for new anti-TB drugs.